2001
DOI: 10.1103/physrevb.63.115408
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between plasmons and the band structure for the Mo(112) surface

Abstract: "Interplay between plasmons and the band structure for the Mo(112) surface" (2001). Peter Dowben Publications. 25. http://digitalcommons.unl.edu/physicsdowben/25 Interplay between plasmons and the band structure for the Mo"112… surface Recent photoemission and inverse photoemission results for the Mo͑112͒ surface are discussed in the framework of the calculated band structure. For the Mo͑112͒ surface, the main photoemission features combine contributions from both the surface and the bulk. Except for those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
29
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 57 publications
12
29
0
Order By: Relevance
“…33,34 The parallel component of the wave vector (k ʈ ) is determined from the photoelectron ͑or incident electron͒ kinetic energy and the emission ͑or incidence͒ angle as…”
Section: Methodsmentioning
confidence: 99%
“…33,34 The parallel component of the wave vector (k ʈ ) is determined from the photoelectron ͑or incident electron͒ kinetic energy and the emission ͑or incidence͒ angle as…”
Section: Methodsmentioning
confidence: 99%
“…The UP spectrum of the clean Mo͑112͒ surface ͑0͒ is shown for comparison and is in line with the results of a recent angle-resolved photoelectron spectroscopy ͑ARPES͒ and inverse photoelectron spectroscopy ͑IPES͒ study in which the origin of the different peaks in the spectrum is discussed in detail. 50,51 The freshly deposited silica film changes the UP spectrum of the Mo͑112͒ surface substantially. On the basis of He I UP studies of 4:2 coordinated silica modifications reported in the FIG.…”
Section: B Stoichiometry and Valence Bandsmentioning
confidence: 99%
“…The Γ critical point of 2.31 Å −1 (in the second Brillouin zone) indi- cates the small value of the inner potential, much smaller than in most transition metals (including Ni [34]and Mo [35]). The low value is not completely unreasonable, because in general there is no reason to expect the inner potential to be determined by the full bandwidth in a chemical compound.…”
Section: The Cos 2 Bulk Band Structurementioning
confidence: 99%
“…In this regard, CoS 2 resembles the much touted La 0.65 Sr 0. 35 MnO 3 [18], although CoS 2 is less complicated. CoS 2 can be alloyed with the narrow band gap semiconductor FeS 2 to become the highly spin-polarized ferromagnet Fe 1−x Co x S 2 , which more closely resembles an ideal ground-state half-metallic ferromagnet, by "tuning" the Fermi level [12][13][14]19].…”
Section: Introductionmentioning
confidence: 99%